JQuery UI - Sarrion, Eric (O'Reilly, 2012)
With the jQuery UI library, you can apply the power and standards of jQuery to user interface design, complete with interactive elements, animation, and themeable widgets. This concise, code-heavy guide demonstrates how to harness interactive features that HTML5 lacks, including tabs, accordions, and dialog boxes. You'll also learn how to program common but complex tasks, such as managing drag and drop and autocomplete, that make it easier for users to interact with your site. This book provides a quick tour of how jQuery UI can improve your HTML pages, followed by standalone chapters that focus on each of the components in detail. If you're a web developer or designer looking to enrich your website with new features--without having to dive into full-fledged Javascript--jQuery UI is a must. This book covers the following extensions in version 1.8: Tab management Accordion menus Dialog boxes Buttons Progress bars Sliders Date pickers Autocompleters Drag and drop management Selection, resizing, and switching of elements New visual effects.